Analisis Pendapatan Asli Desa (PADesa), Dana Desa (DD) Pada Belanja Desa Bidang Pembangunan Desa (Studi Desa Bringin Kecamatan Wajak Kabupaten Malang) - Hesri Hesri; Muhammad Agus Salim; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is entitled "Analysis of Village Original Income (PADesa), Village Funds (DD) on Village Expenditure in the Field of Village Development (Bringin Village Study, Wajak District, Malang Regency)". The purpose of this study is to identify whether or not there is an increase in Village Original Income (PADes) and Village Funds (DD) which are used for Village Shopping needs for Development every year in Bringin Village, Wajak District, Malang Regency. The object of this study is in the form of a village revenue and expenditure budget report (APBDes) starting from the 2017-2021 period. This research data is from the APBDes of the Bringin Village office, Wajak District, Malang Regency. The analytical technique used in this study is descriptive quantitative. In the results of the inter-achievement analysis of this study, it shows that the Original Village Income and Village Fund have increased every year due to the large number of village needs, especially in village spending in the development sector. Keywords: Village Original Income, Village Funds, Village Expenditure